Synthesis, characterisation of polymer-supported palladium-2-methylimidazole complex catalyst for the hydrogenation of aromatic nitro compounds - Velua, Udayakumar; Stanislaus, Alexander; Virupaiah, Gayathri; Shivakumaraiah; Patil, Kashinath Rangu; Balasubramanian, Viswanathan (Journal of Chemical Research, 2011)
A polymer-supported palladium-2-methylimidazole complex was synthesised and characterised by various physicochemical methods. The complex was successfully used as a catalyst for the hydrogenation of nitrobenzene and a few of its derivatives under ambient conditions. Results reveal that the electronic as well as the steric effects of the substitutent control the rate of hydrogenation of the nitro group in the studied nitro compounds. The kinetics of hydrogenation and the reusability of the catalyst were also studied.
Keywords: aromatic nitro compounds; Hydrogenation; polymer-supported complex catalyst; transition metal complexes

Calixarene based nanocomposite materials for high performance supercapacitor electrode - Waghmode, Babasaheb J.; Soni, Roby; Patil, Kashinath Rangu; Malkhede, Dipalee D. (New Journal of Chemistry, 2017)
A functionalised calixarene {4-Sulphatocalix [6] arene Hydrate (SC6)} stabilises MoS2/partially reduced graphene oxide (rGO) nanosheet. Such stabilised SC6-rGO/SC6-MoS2 and SC6 doped polyaniline (PANI) together forms a nanocomposite hybrid material for supercapacitor electrode. It was fabricated by an in situ polymerization method. Transmission electron microscopy (TEM) results suggest that PANI nanostructures grow homogeneously onto the surfaces of SC6 functionalised MoS2. Calixarene acts as a dopant for PANI as well as a stabiliser for the 2D nanosheets of rGO/MoS2. The characterisation of composites together with basic components was done by using various techniques namely, solid-state FT-IRspectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The electrochemical performance was analysed by cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectrometry (EIS). It was found that the SC6 functionalised MoS2 and SC6 doped PANI formed a uniform nanocomposite. The synthesised composites show high specific capacitance (691 F/g) and good cycling stability during the charge-discharge process when used as supercapacitor electrodes. The improvement in electrochemical performance of composites is assigned to synergistic effect of SC6 stabilised MoS2 and doped PANI. Our investigation highlighted the importance of use of calixarene in composites for above stated supercapacitor performance. The role of calixarene in the present study opens a way for the application of alike materials in the composite supercapacitors for energy storage applications.

Composite thin film of simultaneously formed carbon and SnO2 QDs for supercapacitance application - Jadhav, Aarti; Patil, Sagar; Patil, Kashinath Rangu; Sathaye, Shivaram Dattatray; Rode, Chandrashekhar Vasant (New Journal of Chemistry, 2018)
Composite material with uniform size and structure is a critical asset that decides its properties like charge transfer, thermal, photoluminescence, mechanical, etc. and consequently the applications. Here for the first time, we report the concept of flame/combustion at liquid-liquid interface to synthesize in situ, thin film formation of composite consisting of two or more quantum dots. Synthesis of thin films of a composite containing C and SnO2 QDs having particle sizes below 3 nm was successfully done. As compared to a single quantum dots system, the formed composite showed significantly improved specific capacitance due to the synergistic effect arising from strong interaction between C and SnO2 QDs. This was confirmed by XPS, UV visible spectroscopy and photoluminescence spectra. Moreover, it was confirmed that even after 1000 charge/discharge cycles, the interaction between C and Sn remained unaltered; indicating significant stability of capacitance. Some of the advantages of this method include one step, eco-friendly process at ambient conditions. The generality of the method was established by synthesizing C-ZnO and C-TiO2 composite thin film. This new approach can be extended to form many other valuable composite thin films for various applications.